(untitled) (Research, Society and Development, 2021)
Teeth with extraordinary length are a rare condition that complicates endodontic procedures due to the difficult in being reached the working length and making the adequate preparation of the root canal, once there are no endodontic instruments longer than 31 mm commercially available. This study presents a description of technical adaptations for endodontic preparation of a maxillary canine with 39.59 mm of length. The procedures adopted were based on the consultation of the literature regarding the treatment of long teeth, and included endodontic instrument adaptation and changing the reference point of the instrument. This study shows that extremely long teeth can be successfully instrumented endodontically using the described clinical techniques.